2015
DOI: 10.1155/2015/587378
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Intramedullary Nailing Surgery Increased the Mitochondrial DNA Release That Aggravated Systemic Inflammatory Response and Lung Injury Induced by Elderly Hip Fracture

Abstract: Conventional concept suggests that immediate surgery is the optimal choice for elderly hip fracture patients; however, few studies focus on the adverse effect of immediate surgery. This study aims to examine the adverse effect of immediate surgery, as well as to explore the meaning of mtDNA release after trauma. In the experiment, elderly rats, respectively, received hip fracture operations or hip fracture plus intramedullary nail surgery. After fracture operations, the serum mtDNA levels as well as the relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 47 publications
2
24
0
1
Order By: Relevance
“…Various studies have demonstrated that mtDNA is a critical activator of inflammation and the innate immune system (14,31). Some research reported that cellular injury released mtDNA into blood, which is a key link between trauma, inflammation, soluble immune response suppressor (SIRS) and acute lung injury in polytrauma patients and the elderly hip fracture model (12,13,16). mtDNA contains unmethylated CpG motifs that exhibit immune stimulatory capacities (31).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various studies have demonstrated that mtDNA is a critical activator of inflammation and the innate immune system (14,31). Some research reported that cellular injury released mtDNA into blood, which is a key link between trauma, inflammation, soluble immune response suppressor (SIRS) and acute lung injury in polytrauma patients and the elderly hip fracture model (12,13,16). mtDNA contains unmethylated CpG motifs that exhibit immune stimulatory capacities (31).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence has suggested that hip fracture induces substantial mitochondrial (mt)DNA release, systemic inflammatory response and lung injury in the elderly (12). Immediate intramedullary nailing surgery could aggravate the above pathological states (12). Similarly, it was previously demonstrated by the current group that hip fracture and surgery also elevate systemic proinflammatory mediators in elderly patients, and the inflammatory response may serve a key role in postoperative lung dysfunction (13).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…СВР определялась «первым ударом» и не была связана с выполнением операции. Но в эксперименте установ-лено, что после раннего интрамедуллярного остеосин-теза бедренной кости увеличивается выброс в кровь митохондриальной ДНК, уровень которой коррелирует с уровнями цитокинов (TNF-α и IL-10) в сыворотке крови и выраженностью патогистологических измене-ний в легких [39].…”
Section: преимущества и опасности раннего интрамедуллярного остеосинтезаunclassified